2017
DOI: 10.1038/ng.3849
|View full text |Cite
|
Sign up to set email alerts
|

Genomic consequences of aberrant DNA repair mechanisms stratify ovarian cancer histotypes

Abstract: We studied the whole-genome point mutation and structural variation patterns of 133 tumors (59 high-grade serous (HGSC), 35 clear cell (CCOC), 29 endometrioid (ENOC), and 10 adult granulosa cell (GCT)) as a substrate for class discovery in ovarian cancer. Ab initio clustering of integrated point mutation and structural variation signatures identified seven subgroups both between and within histotypes. Prevalence of foldback inversions identified a prognostically significant HGSC group associated with inferior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
288
5
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 240 publications
(319 citation statements)
references
References 54 publications
21
288
5
5
Order By: Relevance
“…A recent study in localized prostate cancer demonstrated clusters of genomic rearrangements each occurring in 5–6% of samples (Fraser et al, 2017). In addition, previous studies have demonstrated that SVs may define subtypes of ovarian, pancreatic, and breast cancers (Nik-Zainal et al, 2016; Patch et al, 2015; Waddell et al, 2015; Wang et al, 2017). Of note, the majority of SVs involve intergenic or intronic noncoding regions of the genome and are not captured by exome sequencing or transcriptome analysis.…”
Section: Introductionmentioning
confidence: 98%
“…A recent study in localized prostate cancer demonstrated clusters of genomic rearrangements each occurring in 5–6% of samples (Fraser et al, 2017). In addition, previous studies have demonstrated that SVs may define subtypes of ovarian, pancreatic, and breast cancers (Nik-Zainal et al, 2016; Patch et al, 2015; Waddell et al, 2015; Wang et al, 2017). Of note, the majority of SVs involve intergenic or intronic noncoding regions of the genome and are not captured by exome sequencing or transcriptome analysis.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, there is a clinical need to understand the key molecular drivers of cancer subsets such as those arising from endometriosis, which may drive treatment recommendations. Currently, whole genome sequencing analysis of ovarian cancer samples allows stratification into histotypes, including subclassification of OEA into tissues that are microsatellite stable and those with microsatellite instability . While large amounts of genomic data have been generated based on histotype, there is limited information regarding the molecular contribution of the endometriotic tumor microenvironment on OEA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, use of single nucleotide polymorphisms in microRNA machinery genes, mature microRNA molecules, or microRNA binding sites in genes to determine the risk of EOC diagnosis has been not been replicated clinically. Larger studies and grouping samples according to newly published genetic changes (4) instead of histotype or grade may allow for results that are more replicable.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular landscape of each histotype of EOC is distinct (3, 4). However, all patients are treated similarly with standard of care debulking surgery and chemotherapy regimens, with dismal “cure” rates of 20% (1).…”
Section: Microrna Molecules As Clinical Biomarkers For Eocmentioning
confidence: 99%
See 1 more Smart Citation